Exploring the expression of Pseudomonas aeruginosa genes directly from sputa of cystic fibrosis patients. (1st November 2015) - Barthe, C.; Nandakumar, S.; Derlich, L.; Macey, J.; Bui, S.; Fayon, M.; Crouzet, M.; Garbay, B.; Vilain, S.; Costaglioli, P.
Abstract: Acquisition of Pseudomonas aeruginosa is known as a negative prognostic factor in patients with cystic fibrosis. We started a pilot study to evaluate Ps. aeruginosa gene expression directly from the sputum of infected patients. Total RNA was purified from 15 sputum samples collected from 10 patients, and the expression levels of five genes from Ps. aeruginosa were measured by RT‐qPCR. Expression of algD, algR, antB, lasB and pqsA genes was determined in sputa that contained Ps. aeruginosa cells. The resultant data provided an overview of the expression of these genes in CF patients. Except for the correlation between algD expression and the mucoid phenotype, the gene expression profile could not be associated with the clinical status of patients. However, beyond the heterogeneity of the Ps. aeruginosa phenotype in sputum, we observed a correlation between the expression of antB and pqsA and a low level of lasB transcripts. Significance and Impact of the Study: Pseudomonas aeruginosa infection leads to high morbidity and mortality in cystic fibrosis patients. The identification of Ps. aeruginosa ‐assigned factors is important to eradicate the colonization. We started a pilot study to evaluate the gene expression of Ps. aeruginosa directly from the sputum of infected patients. Preliminary results suggest that beyond the heterogeneity of the Ps. aeruginosa phenotype in sputum, we observe a correlation between the expression of antB and pqsA and a low level of lasB transcripts. This approach could shed some light on the behaviour of Ps. aeruginosa during pulmonary infection and may reveal some important elements for optimizing therapy.